PENERAPAN MANAJEMEN RISIKO PADA PENGELOLAAN LIMBAH PABRIK TAHU XYZ MENGGUNAKAN ISO 31000: IMPLEMENTATION OF RISK MANAGEMENT IN WASTE TOFU FACTORY XYZ USING ISO 31000 - Fathur Rahman Min Ibad; Muhammad Dandi Dwi Cahyo Putra (Program Studi Teknologi Informasi, 2021)
Risk is a situation where there is an element of uncertainty and an element of danger, a result or consequence of an ongoing process or future event. A risk can occur because there is no or lack of information about something that will happen in the future, whether it is in the form of a good thing or something that is detrimental. Risk management is all process activities carried out solely to minimize and even prevent risks to the industry. This includes identifying, planning, strategy, action, monitoring and evaluation of negative things that are likely to happen to the business. Risk management is an approach that adopts a consistent system to manage all risks faced by a company. Tofu Factory XYZ is an industry that operates in the production of soy milk processing into tofu. Of course, XYZ Tofu Factory has many risks. Especially at the time of disposal of liquid waste during the production process, which will certainly have an impact on the environment if not handled properly. In the application of risk management at the XYZ Tofu Factory using ISO 31000 standards, the researcher used apu wood media with the aim of conducting an environmental risk management analysis..